Rapid scientific communication in times of pandemic: the attention of pre-prints online about Covid-19 - Santos Rocha, Eduardo; Ferreira Araújo, Ronaldo (Advanced Notes in Information Science, 2022)
This research analyzes the online attention received by preprints about Covid-19 shared on Twitter between 2020 and 2021. thematic category identifying the number of tweets received by each class. We used literature review, documental research, content analysis, and altmetric analysis procedures. We classified the preprints in 'Clinical Studies', 'Prevention', 'Transmission', 'Treatment-Drugs', 'Variants' and 'Others', disseminated more than 776,000 times. The categories 'Clinical Studies' and 'Prevention' were the ones that registered the most searches (53%) and most shares (57%). The study showed that studies related to the prevention of Covid-19 figured as the subjects of greatest interest to the scientific community and received greater attention from Twitter users. We concluded that altmetrics has provided a greater understanding of the impact of studies on Covid-19 and that thematic orientation contributes to a better understanding of the online attention directed to these studies.